Why organizational loyalty programs cannot prevent switching. Issue 2 (10th February 2020) - Mattison Thompson, Frauke; Tuzovic, Sven
Abstract : Purpose: The purpose of this study is to investigate the extent to which loyalty programs can prevent switching, and how individual level cultural values impact this. Loyalty programs are designed to create switching costs, which reduce customers' desire to leave. However, in practice, these programs are often misapplied; that is, most companies inadvertently treat all customers as equal. While ample research has examined the role of loyalty reward programs in facilitating customer loyalty, little is known about the extent to which individual-level cultural values moderate customer loyalty measures of trust and affective commitment and how this impacts the effectiveness of loyalty programs; that is, consumers' intentions to "stick" with the program or to switch. Design/methodology/approach: This study uses a quasi-experiment combined with an extensive survey to collect the data. Findings: Based on data collected from one industrial country and four emerging countries, the results show that loyalty programs do not universally prevent switching behavior. Instead, this study finds that individual-level uncertainty avoidance and collectivist values significantly moderate the effects. Originality/value: This study helps advance the understanding of how international retailers can increase their loyalty program effectiveness and reduce customer switching to competitors.